Initial results from WING, the continuous GPS network in the western Pacific area - Kato, Teruyuki; Kotake, Yoshiko; Nakao, Shigeru; Beavan, John; Hirahara, Kazuro; Okada, Masami; Hoshiba, Mitsuyuki; Kamigaichi, Osamu; Feir, Renato B.; Park, Pil Ho; Gerasimenko, Mikhail D.; Kasahara, Minoru (Geophysical research letters, 1998)
To investigate tectonic deformation in the western Pacific, a continuous GPS tracking network has been established, and named the Western Pacific Integrated Network of GPS (WING). Between 1995 and March 1997 we establised ten new sites. Data for the period July 1995 to October 1996 were analyzed, together with data from International GPS Service for Geodynamics (IGS) global sites, to estimate daily coordinates. A fiducial‐free approach was used to obtain the most accurate baseline estimates. To fix the estimated coordinates to the terrestrial reference frame, the Tsukuba IGS site is assumed to be moving westward relative to the stable Eurasian continent at ∼2 cm/yr according to Heki's [1996] estimate. We find that: (1) velocities of sites well within oceanic plates are in good agreement with rigid plate motion models; (2) sites close to plate boundaries are all affected by the deformation at those boundaries, among which back‐arc rifting (spreading) is clearly visible at the Mariana and Okinawa troughs; (3) sites in eastern Asia are moving east to east‐southeast relative to the stable Eurasian continent, suggesting long distance effects of the northward collision of India with Asia.